2009
DOI: 10.1152/ajpheart.01213.2008
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate-fortified cardioplegia evokes myocardial erythropoietin signaling in swine undergoing cardiopulmonary bypass

Abstract: Pyruvate-fortified cardioplegia protects myocardium and hastens postsurgical recovery of patients undergoing cardiopulmonary bypass (CPB). Pyruvate reportedly suppresses degradation of the alpha-subunit of hypoxia-inducible factor-1 (HIF-1), an activator of the gene encoding the cardioprotective cytokine erythropoietin (EPO). This study tested the hypothesis that pyruvate-enriched cardioplegia evoked EPO expression and mobilized EPO signaling mechanisms in myocardium. Hearts of pigs maintained on CPB were arre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…162 Here, pyruvate-enriched cardioplegia stabilized HIF-1α content, which paralleled robust myocardial mRNA expression and synthesis of EPO. Elements of EPO’s intracellular signaling cascades, Erk and eNOS, were activated following pyruvate cardioplegia.…”
Section: Induction Of Erythropoietin and Neuroprotection By Pyruvatementioning
confidence: 82%
“…162 Here, pyruvate-enriched cardioplegia stabilized HIF-1α content, which paralleled robust myocardial mRNA expression and synthesis of EPO. Elements of EPO’s intracellular signaling cascades, Erk and eNOS, were activated following pyruvate cardioplegia.…”
Section: Induction Of Erythropoietin and Neuroprotection By Pyruvatementioning
confidence: 82%
“…The role of HIF in cell survival from I/R injury has been widely reported 14,15,21,41 . MB significantly increases HIF-1α protein content compared to both normoxic and OGD control groups (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, pyruvate can indirectly contribute to ROS detoxification by inducing synthesis of erythropoietin, a cytokine with antioxidant properties (Toba et al, 2012). We reported that pyruvate increases HIF-1-driven mRNA expression and protein content of erythropoietin by stabilizing the O 2 -regulated HIF-1α (Ryou et al, 2009, 2012). In accordance with pyruvate’s antioxidant properties, the current study demonstrated that pyruvate enhanced NADPH/NADP + redox state, suppressed ROS generation after OGD and reoxygenation, and maintained the integrity of vascular endothelial tight junctions.…”
Section: Discussionmentioning
confidence: 96%